Competing Models of Disability: Medicalization’s Ambivalent Effects on the Paralympic Movement - Evan T. Baughman (Socius)
Disability is predominantly understood as a medical problem. Since the 1980s, disability scholars have critiqued the medicalization of disability to illuminate disability’s social and political dimensions. Building on this tradition, the present article analyzes the Paralympic movement to call sociological attention to how medicalization affects disabled social movements, cultural production, and cultural practices. The author draws from interviews with Paralympic athletes and coaches alongside primary historical sources to identify and evaluate medicalization’s effects on the Paralympic movement. Findings show that medicalization both enabled and constrained the Paralympic movement. The medicalization of spinal cord injuries developed lifesaving treatments and mobilized disability sport as rehabilitative treatment to mold patients into healthy, productive “taxpayers.” Framing disability sport as rehabilitation catalyzed the medicalization of the Paralympic movement, as the medical profession facilitated the formation and maintenance of the movement. This understanding of disability sport reflected the clinical nature of medicine and rehabilitation’s approach to disability. However, the clinical approach to Paralympic sport conflicted with Paralympians’ desire for high-performance disability sport and recognition as elite athletes. Medical governance subsequently marginalized Paralympians within Paralympic organizations and limited Paralympians’ ability to develop their sports beyond mere rehabilitation. These findings are consistent with Mauldin’s conceptualization of medicalization as “ambivalent.”